Managing Stock In Warehouse: A Case Study of A Retail Industry In Jakarta - Paul, Yericho; Lestari, Yuliani Dwi (Journal of Business and Management, 2015)
Abstract. Purpose – The purpose of this paper is to inform the warehouse management of PT. Chintaka Bumi Pertiwi, so that the company knows which processes or activities within the current warehouse work process is having problems in terms of performance or causing stock inaccuracy and to propose solution of the problems. Methodology / Approach – The methodology used for research is by interviewing the Logistics and Shipment Chief, Supervisor, and Administrator of PT. Chintaka Bumi Pertiwi warehouse resulting in the current warehouse work process, implemented SOP, number of goods lost during stock inaccuracy, number of inaccuracy case, types of goods lost, warehouse layout, goods placement. The data from interview process then compared to the actual data gathered through direct observation to identify current problems occurring and to see whether there are connections between these data. The compared result of both data collection then analyzed to see the real cause of problems within the company and the proper solution on how to improve current system by solving the identified problem. Last, recommendations will be given to the company on how to do the proposed solutions before and during the implementation. Findings – The inaccuracy case of the company increased by 11.3% with approximate value loss due to goods lost during the stock inaccuracy case in summed up around 30 million Rupiah. The current work processes is experiencing problems caused by procedure, company regulations, and the level of control applied within storage section. Research Limitation – The limitation of this research is the product types, which are CBK4401, CBK3402, CBK6402, CBG6301, CBG6302, and CBG1305 with the highest amount of inaccuracy case among other products; only focusing on the work processes of the warehouse; and the data from 2013 to 2014.